Teratoma Mimicking Myelolipoma in Adrenal Region (Pulse, 2014)
A 19-year-old female presented with backache and left hypochondralgia on and off for one year. Complete blood counts, urinalysis and culture were negative. Ultrasonogram revealed normal kidney and urinary bladder along with a lobulated solid mass at left adrenal region with focal peripheral calcification. Based on the findings, CT scan was advised. CT scan without contrast showed a mass in left adrenal region of approx 3.3x3.2x2.6 cm with punctuate calcification in the wall as well as within the mass. The mass was well encapsulated with predominant fat attenuation interspersed with septae. The left adrenal was not separately identified, hence a presumptive diagnosis of adrenal myelolipoma was considered. The patient underwent left adrenalectomy and the specimen was sent for histopathological examination. Histopathology showed a mass adherent to normal adrenal showing several well differentiated ectodermal structures (tooth, hair follicles, sweat and sebaceous glands etc) consistent with a mature teratoma. The patient recovered uneventfully and is doing well at present. DOI: http://dx.doi.org/10.3329/pulse.v5i1.20192 Pulse Vol.5 January 2011 p.54-56